Cuttability of coal from the Soma coalfield in Turkey. (January 2015) - Bilgin, Nuh; Balci, Cemal; Copur, Hanifi; Tumac, Deniz; Avunduk, Emre
Highlights: Chemical, thermal and mechanical and cutting properties of coal. Net calorific value, volatile matter, fixed carbon and ash content of coal. Cutting tests to measure cutting and normal forces including specific energy. Coal cutting in a mechanized production system with shearers.